Enhanced recovery after surgery protocol for prostate cancer patients undergoing laparoscopic radical prostatectomy. Issue 1 (January 2019) - Lin, Chunhua; Wan, Fengchun; Lu, Youyi; Li, Guojun; Yu, Luxin; Wang, Meng
Objective: To determine the value of an enhanced recovery after surgery (ERAS) protocol for prostate cancer patients undergoing laparoscopic radical prostatectomy (LRP). Methods: We conducted a retrospective cohort study using clinical data for 288 patients who underwent LRP in our hospital from June 2010 to December 2016. A total of 124 patients underwent ERAS (ERAS group) and the remaining 164 patients were allocated to the control group. ERAS comprised prehabilitation exercise, carbohydrate fluid loading, targeted intraoperative fluid resuscitation and keeping the body warm, avoiding drain use, early mobilization, and early postoperative drinking and eating. Results: The times from LRP to first water intake, first ambulation, first anal exhaust, first defecation, pelvic drainage-tube removal, and length of hospital stay (LOS) were all significantly shorter, and hospitalization costs and the incidence of postoperative complications were significantly lower in the ERAS group compared with the control group. No deaths or reoperations occurred in either group, and there were no readmissions in the ERAS group, within 90 days after surgery. Conclusion: ERAS protocols may effectively accelerate patient rehabilitation and reduce LOS and hospitalization costs in patients undergoing LRP.